Assembly of Na3V2(PO4)2F3@C nanoparticles in reduced graphene oxide enabling superior Na+ storage for symmetric sodium batteries. Issue 6 (15th January 2018) - Yao, Ye; Zhang, Lu; Gao, Yu; Chen, Gang; Wang, Chunzhong; Du, Fei
Abstract : Symmetrical full cell of NVPF@C@rGO as both cathode and anode could light the LED lamp successfully after the 25th charge–discharge cycle at 1C. Abstract : Reduced graphene oxide (rGO) was used to encapsulate Na3 V2 (PO4 )2 F3 @Carbon nanoparticles to overcome its inherent low electronic conductivity and achieve superior sodium storage performance. This as-prepared cathode delivers a remarkable rate performance with a discharge capacity of ca. 64 mA h g −1 at 70C and an ultra-long-term cyclability over 4000 cycles with great capacity retention of 81% at 30C. This excellent performance can be attributed to the favorable combination of fast ionic conductivity of the NASICON structure and the interpenetrating conductive carbon framework; thus bringing a good pseudocapacitive quality to this material. Furthermore, thanks to the good sodium storage properties at low potential, a symmetric full cell can be assembled using Na3 V2 (PO4 )2 F3 @C@rGO as both cathode and anode. The full cell delivers a high discharge capacity of 53 mA h g −1 at 20C rate, further demonstrating the feasibility of this hybrid material for smart grids.